Prenatal Testing and Pregnancy Termination Among Muslim Women Living in Israel Who Have Given Birth to a Child with a Genetic Disease - Amiel, Aliza (Journal of religion and health, 2023)
The aim of the study was to investigate whether a Muslim woman with a child afflicted with a genetic disease who is living at home would perform more prenatal tests and pregnancy terminations as opposed to a woman with a normal child living at home, and what demographic characteristics, if any, influenced this decision. The study included 771 Muslim women; 37.1% lived with a child afflicted with a genetic disease; and 62.9% did not. Muslim women with a child affected with a genetic disease living at home will undergo more prenatal testing and more pregnancy terminations. Village dwellers were more religious and consulted further with a religious authority. More city dwellers underwent prenatal tests and pregnancy terminations and received more health care and genetic counseling. In the villages populated by Muslims, more genetic counselling must be given, accompanied by guidance from religious Muslim authorities.